The role of m6A RNA methylation in infectious diseases - Yadav, Nidhi; Khan, Reshma; Goyal, Sandeep; Kumari, Rajesh (Frontiers in RNA Research, 2025)
Among over 170 known RNA modifications, N6-methyladenosine (m6A) stands out as the most ubiquitous and extensively studied modification, found in different cellular RNA. The m6A plays a pivotal role in regulating RNA nuclear export, stability, secondary structure, translation, and degradation eventually determining the gene expression. The m6A modification is controlled by three classes of enzymes: “writers”, “erasers”, and “readers” which not only play a role in adding and removing the methyl group but also help in recognizing and interpreting the methylation marks. Although m6A has been widely studied in the context of metabolic diseases and cancers, its influence on infectious diseases remains under-explored. The infection cycle of several pathogens, including viruses, bacteria, and parasites is regulated by the m6A methylation machinery. In this review, we will not only explore the existing knowledge about m6A methylation but also its influence in shaping the pathogen life cycle paving our way to therapeutic aspects to mitigate infectious diseases.